2016
DOI: 10.1007/s00595-016-1410-9
|View full text |Cite
|
Sign up to set email alerts
|

Comparative benefits of laparoscopic surgery for colorectal cancer in octogenarians: a case-matched comparison of short- and long-term outcomes with middle-aged patients

Abstract: We suggest that advanced age should not be a contraindication for LCS, even for complex procedures, such as laparoscopic rectal resection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 32 publications
0
10
0
Order By: Relevance
“…Furthermore, a systemic review of 28 studies with a total of 34,194 patients who underwent colorectal surgeries concluded that incidence of postoperative morbidity and (54). Furthermore, a case-matched control study showed that, despite octagenarians (age !80 years) having expected higher American Society of Anesthesia score than middleaged controls (age 60-69 years), there were no significant differences in both morbidity incidence or 5-year cancerspecific survival in both cohorts (55). Although data suggest feasibility and utility of laparoscopic surgery in elderly patients, future randomized studies in ECPs with LARC comparing laparoscopic versus open surgery with specific attention to the preoperative CRM status are warranted, to better select patients for the optimal surgical technique.…”
Section: Surgery Alonementioning
confidence: 79%
“…Furthermore, a systemic review of 28 studies with a total of 34,194 patients who underwent colorectal surgeries concluded that incidence of postoperative morbidity and (54). Furthermore, a case-matched control study showed that, despite octagenarians (age !80 years) having expected higher American Society of Anesthesia score than middleaged controls (age 60-69 years), there were no significant differences in both morbidity incidence or 5-year cancerspecific survival in both cohorts (55). Although data suggest feasibility and utility of laparoscopic surgery in elderly patients, future randomized studies in ECPs with LARC comparing laparoscopic versus open surgery with specific attention to the preoperative CRM status are warranted, to better select patients for the optimal surgical technique.…”
Section: Surgery Alonementioning
confidence: 79%
“…Laparoscopic approaches to rectal cancer have increased over the past 20 years with laparoscopy providing decreased narcotic intake, shorter hospital stays, faster return to activity compared to those undergoing open surgery (107)(108)(109). A number of studies have specifically looked at this comparison in the elderly population (110)(111)(112)(113). Manceau et al evaluated 446 consecutive patients grouping them into 10-year intervals from under 45 to older than 64 years.…”
Section: Laparoscopic Surgerymentioning
confidence: 99%
“…They similarly found that the ASA score was significantly higher in the octogenarian group but this did not correlate with increased post-operative complications and longterm cancer specific survival (91% in the octogenarian group and 95.7% in the case matched controls). There was an increased rate of permanent stoma in the elderly group from either abdominoperineal or Hartmann's procedure compared to the middle-aged group (112). Recently, comparison between laparoscopic and open surgery has been evaluated in two large multicenter trials, ALACART and ACOSOG Z6051 with both showing that laparoscopic surgery did not meet non-inferiority for rectal cancer patients (114,115).…”
Section: Laparoscopic Surgerymentioning
confidence: 99%
“…In many institutions, laparoscopic surgery is the standard treatment for patients with colon cancer because its oncological safety in these patients has been proven in randomized trials . As laparoscopic surgery in colon cancer patients has become more common and its safety and feasibility confirmed, its application range has been expanded to include elderly patients …”
Section: Introductionmentioning
confidence: 99%
“…2 As laparoscopic surgery in colon cancer patients has become more common and its safety and feasibility confirmed, its application range has been expanded to include elderly patients. 3 Our institution introduced single-port laparoscopic colectomy (SPLC) in August 2010. From our initial experiences, we concluded that SPLC could be applied to colon cancer with favorable short-term clinical outcomes.…”
Section: Introductionmentioning
confidence: 99%